Method for improving laser directional energy deposition forming quality of heterogeneous materials
By establishing a three-dimensional visual model in multi-material additive manufacturing and real-time adjustment of material component proportion and path planning, the problem of transition mutation of material component and coarse structure of sedimentary layer is solved, high forming quality and continuity are achieved, and differentiation is improved. The manufacturing effect of quasi-isomer materials.
Patent Information
- Application Number
- CN202411215899.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-30
- Publication Date
- 2024-12-27
AI Technical Summary
In multi-material additive manufacturing, the prior art is difficult to achieve continuous gradual transition between material components, resulting in problems such as coarse structure, deformation and cracking of the deposited layer, limiting the manufacturing application of large and complex structural parts.
By establishing a three-dimensional visual model, selecting appropriate nanoparticles as raw materials, and adjusting the proportion of material components and path planning forms in real time, regulating the thermal cycle of the directional energy deposition process, ensuring the material components-inherent properties-used performance in three-dimensional space Continuously controllable.
A high-forming quality heterogeneous material deposited members is achieved, reducing residual stress and deformation, and improving the continuity and performance consistency of the deposited members.
Smart Images

Figure CN119187601A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for improving the forming quality of heterogeneous and heterogeneous materials by laser directional energy deposition, and belongs to the field of multi-material additive manufacturing. Background Art
[0002] Additive manufacturing technology manufactures parts by "layered slicing and stacking layer by layer"; this technology has huge advantages over traditional manufacturing technology and can realize free and rapid manufacturing of parts in a short period of time, providing a new solution for the manufacture of large and complex structures; with the rapid development of modern industry, additive manufacturing of large and complex structural parts is developing towards lightweight, functional integration, and intelligence; however, parts made of a single material are difficult to meet the needs of the rapidly developing manufacturing industry, and this is when multi-material additive manufacturing emerged.
[0003] At present, the research on multi-material additive manufacturing is still focused on the powder bed fusion (PBF) technology with powder bed spreading as its technical feature. For example, a patent application (patent number: 201910980121.X) discloses a multi-material powder spreading device for laser powder bed melting additive manufacturing; the patent application aims to automatically lay the corresponding materials at the corresponding positions according to the material sub-model during the powder laying process, without the need for powder suction and secondary powder laying. The laying process is rapid, the steps required for powder laying are simplified, and the powder laying efficiency is significantly improved; the limitation of this method is that there will be an obvious mutation layer between the upper material and the lower material, and a continuous gradual transition between material components cannot be achieved.
[0004] In addition, when the additive manufacturing technology forms parts, the deposited layer undergoes complex thermal cycles. During the deposition process, due to unreasonable path planning, the deposited layer inevitably has problems such as coarse structure, deformation and even cracking; the above problems limit the application of multi-material additive manufacturing in the manufacture of large and complex structural parts; currently, the solutions to the above problems are mostly focused on introducing new processes based on existing processes, which undoubtedly increases the production cycle and manufacturing cost of parts; for example, a patent application (patent application number: 201910980121.X) discloses a method for ultrasonic vibration-assisted arc additive manufacturing of multi-material components; the core of this technology is to combine an ultrasonic vibration-assisted system with a multi-material arc additive manufacturing system, and to promote the combination of different materials, adjust the distribution of particle reinforcement phases, eliminate cracks and reduce porosity by real-time adjustment of ultrasonic vibration parameters during the manufacturing process, so as to improve the organizational morphology and physical and chemical properties of multi-material components.
[0005] In order to solve the problems of sudden transition of material components between adjacent layers, coarse deposited layer structure, excessive residual stress in deposited components, etc., the present invention proposes a method for achieving continuous controllability of "material components-inherent properties-usage performance" in three-dimensional space for deposited components while ensuring high forming quality. Summary of the invention
[0006] The present invention provides a method for improving the forming quality of heterogeneous materials by laser directed energy deposition, which mainly comprises the following steps:
[0007] (1) Establish a three-dimensional visualization model of the deposition component and select different material components according to its required service performance;
[0008] (2) adding trace amounts of nanoparticles to pre-selected material components as raw materials for the deposition components;
[0009] (3) According to the service performance required by different parts of the deposition component, each material component and its proportion are fed back in real time, and the above information is fed back to the control end of the multi-material intelligent manufacturing system in real time so that the system can adjust the proportion of each material component in real time;
[0010] (4) Considering both material and structural factors, selecting a reasonable path planning form, and regulating the thermal cycle of the directed energy deposition process, thereby reducing the residual stress and deformation of the component and making it more evenly distributed, thereby improving the forming quality of the deposited component;
[0011] (5) The multi-material intelligent manufacturing system will form directed energy deposition components according to the pre-set path planning form; under the premise of ensuring high forming quality, the deposition components will realize the continuous controllability of "material components-inherent properties-usage performance" in three-dimensional space.
[0012] Preferably, the present invention performs calculations based on the two-dimensional lattice mismatch theoretical model established by Bramfitt, and proposes suitable nanoparticles for different materials; the calculation formula is as follows:
[0013]
[0014] Where: is the mismatch degree, is the interatomic distance in a low-index direction on a low-index surface of the substrate, is the atomic distance in a low-index direction on a low-index surface of the nucleation phase, and θ is the angle between these two low-index directions; according to Bramfitt theory, when It is an effective nucleation core; is moderately effective; when When the nucleation phase is formed on a heterogeneous nucleation substrate, it is most effective; therefore, in the selection of nanoparticles, the mismatch degree should be minimized.
[0015] Preferably, in step (2) of the present invention, both material factors and structural factors are considered to select a reasonable path planning form, which is as follows:
[0016] Material factors:
[0017] Taking the thermophysical parameters of copper as the boundary, for materials with a thermal expansion coefficient greater than that of copper, partition scanning or symmetrical scanning paths are used; for materials with a larger thermal expansion coefficient (greater than copper), large and uneven deformation will occur during the deposition process, so partition scanning and symmetrical scanning paths are preferably used to reduce deformation.
[0018] For materials with thermal conductivity greater than copper and Young's modulus less than copper, a shorter path planning form is used;
[0019] Structural factors:
[0020] For single-channel multi-layer thin-walled structures, a reciprocating scanning path planning form is adopted to make the heat distribution more uniform, thereby reducing warping and deformation.
[0021] For multi-channel and multi-layer structures, the path planning form of alternating scanning paths or partitioned scanning is adopted;
[0022] For large metal components with dimensions up to meters, a symmetrical scanning path is used.
[0023] Beneficial effects of the present invention
[0024] (1) The present invention prepares heterogeneous and heterogeneous materials based on laser directed energy deposition technology, and while ensuring high forming quality, enables the deposited components to achieve continuous controllability of "material composition-inherent properties-usage performance" in three-dimensional space.
[0025] (2) The appropriate nanoparticles for different material components are calculated through the two-dimensional lattice mismatch theoretical model.
[0026] (3) Reasonable path planning forms are proposed for different materials and structures to regulate the residual stress and deformation induced by the directed energy deposition thermal cycle. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] By reading the detailed description of the preferred embodiments below, the advantages of the method proposed by the present invention will become clear to those skilled in the art. The accompanying drawings are only used to illustrate the preferred embodiments and are not to be considered as limiting the present application.
[0028] Figure 1 A flow chart of the method of the present invention;
[0029] Figure 2The schematic diagram of the structure of the multi-layer and multi-channel rotating body prepared in the preferred embodiment 1 of the present invention and the path planning form;
[0030] Figure 3 Schematic diagram of the multi-layer and multi-channel block structure and path planning form prepared in the preferred embodiment 2 of the present invention. DETAILED DESCRIPTION
[0031] The specific implementation of the present invention is further described in detail below in conjunction with the accompanying drawings and examples. The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention.
[0032] Example 1
[0033] This embodiment takes the laser directed energy deposition of Ni-Ti-Cu shape memory alloy multi-layer multi-channel cylindrical structure as an example, and provides a method for improving the forming quality of heterogeneous materials by laser directed energy deposition; specifically, the following steps are included:
[0034] (1) Establish a three-dimensional visualization model of a multi-layer cylindrical structure with multiple channels and multiple layers. Figure 2 As shown in (a), Ni powder, Ti powder and Cu powder are selected as material components.
[0035] (2) Selecting TiC nanoparticles as the inoculant for laser directed energy deposition of Ni-Ti-Cu shape memory alloy: Since the crystal structure of TiC is a NaCl-type cubic crystal structure, its lattice constant The three values are and The corresponding lattice constant of Ni-Ti-Cu alloy The three values are and θ takes 0°, 30° and 45°, and the mismatch calculation formula is:
[0036]
[0037] Conclusion The requirement of mismatch degree <15% is met; therefore, TiC nanoparticles can be used as an effective inoculant for Ni-Ti-Cu shape memory alloy; the above three powders and TiC nanoparticles are fully and evenly mixed respectively as raw materials for laser directed energy deposition.
[0038] (3) Take three dividing points from the lower, middle and upper parts of the cylindrical structure and mark them as Ⅰ, Ⅱ and Ⅲ respectively. Figure 2As shown in (a); at the dividing point I, the mass fraction of each component is specified as: Ni:Ti:Cu:TiC=3:3:3:1; at the dividing point II, Ni:Ti:Cu:TiC=5:2:2:1; at the dividing point III, Ni:Ti:Cu:TiC=4:1:4:1; and between regions I, II, and III, the composition of Ni, Ti, and Cu is specified to change continuously to achieve the preparation of heterogeneous and isomeric components.
[0039] (4) Laser directed energy deposition path planning form such as Figure 2 (b) The red arrow indicates the scanning direction of each deposition layer, and the scanning path between two adjacent layers is rotated 67°.
[0040] (5) Selection of laser directed energy deposition process parameters: laser power is 1000 W, scanning speed is 300 mm / min, gas flow rate is 9.0 L / min, and powder particle size is between 53 and 150 μm.
[0041] (6) Through the above-mentioned deposition strategy, high-forming quality, continuous heterogeneous and heterogeneous integrated multi-layer and multi-channel cylindrical structures are prepared based on laser directed energy deposition technology.
[0042] Example 2
[0043] Taking the laser directed energy deposition of Al-Si-Mg-Mn alloy multi-channel multi-layer block structure as an example, a method for improving the forming quality of laser directed energy deposition of heterogeneous materials is provided, which specifically includes the following steps:
[0044] (1) Establish a multi-layer 3D visualization model such as Figure 3 As shown in (a), four kinds of powders, namely Al powder, Si powder, Mg powder and Mn powder, are selected as material components.
[0045] (2) Selecting TiB2 nanoparticles as the inoculant for laser directed energy deposition of Al-Si-Mg-Mn alloy: Due to the lattice constant of TiB2 The three values are and The corresponding lattice constant of Ni-Ti-Cu alloy The three values are and θ takes 0°, 30° and 45°, and the mismatch calculation formula is:
[0046]
[0047] Conclusion The requirement of mismatch degree <15% is met; therefore, TiB2 nanoparticles can be used as an effective inoculant for Al-Si-Mg-Mn alloy; the above five powders and TiB2 nanoparticles are fully and evenly mixed respectively as raw materials for laser directed energy deposition.
[0048] (3) The four vertices of the cube are marked as A, B, C and D, as shown in the figure; at point A, the alloy composition is Al-10Si-1.5Mg-0.8Mn (wt.%), at point B, the alloy composition is Al-15Si-1.5Mg-0.8Mn (wt.%), at point C, the alloy composition is Al-7Si-2Mg-0.8Mn (wt.%), and at point D, the alloy composition is Al-10Si-3Mg-0.5Mn (wt.%); the mass fraction of TiB2 remains unchanged at 2%; within the entire interval, the mass fractions of the four powders Al, Si, Mg, and Mn are specified to change continuously.
[0049] (4) Laser directed energy deposition path planning form such as Figure 3 As shown in (b); each layer of the entire cube is divided into four areas, the red arrow indicates the direction of each deposition layer, and the green arrow indicates the direction of the partition scan.
[0050] (5) Selection of laser directed energy deposition process parameters: laser power is 300 W, scanning speed is 200 mm / min, gas flow rate is 9.0 L / min, and powder particle size is between 53 and 150 μm.
[0051] (6) Through the above-mentioned deposition strategy, high-forming quality, continuous heterogeneous and heterogeneous integrated multi-layer and multi-channel cubic components are prepared based on the laser directed energy deposition process.
[0052] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the scope of the ideas and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for improving the quality of laser directed energy deposition of heterogeneous and heterogeneous materials, characterized by: The specific steps include: (1) Establish a three-dimensional visualization model of the deposition component and select different material components according to its required service performance; (2) adding trace amounts of nanoparticles to pre-selected material components as raw materials for the deposition components; (3) According to the service performance required by different parts of the deposition component, each material component and its proportion are fed back in real time, and the above information is fed back to the control end of the multi-material intelligent manufacturing system in real time so that the system can adjust the proportion of each material component in real time; (4) Considering both material and structural factors, selecting a reasonable path planning form, and regulating the thermal cycle of the directed energy deposition process, thereby reducing the residual stress and deformation of the component and making it more evenly distributed, thereby improving the forming quality of the deposited component; (5) The multi-material intelligent manufacturing system will form directed energy deposition components according to the pre-set path planning form; Under the premise of ensuring high forming quality, the deposited components realize the continuous controllability of "material components-inherent properties-usage performance" in three-dimensional space.
2. The method for improving the quality of laser directed energy deposition of heterogeneous and heterogeneous materials according to claim 1, characterized in that: According to the two-dimensional lattice mismatch theoretical model established by Bramfitt, suitable nanoparticles are proposed for different materials; the calculation formula is as follows: Where: is the mismatch degree, is the interatomic distance in a low-index direction on a low-index surface of the substrate, is the atomic distance in a low-index direction on a low-index surface of the nucleation phase, and θ is the angle between these two low-index directions; according to Bramfitt theory, when It is an effective nucleation core; is moderately effective; when When the nucleation phase is formed on a heterogeneous nucleation substrate, it is most effective; therefore, in the selection of nanoparticles, the mismatch degree should be minimized.
3. The method for improving the quality of laser directed energy deposition of heterogeneous and heterogeneous materials according to claim 1, characterized in that: Considering both material and structural factors, a reasonable path planning form is selected, as follows: Material factors: Taking the thermophysical parameters of copper as the limit, for materials with a thermal expansion coefficient greater than that of copper, a partition scanning or symmetrical scanning path is used; For materials with thermal conductivity greater than copper and Young's modulus less than copper, a shorter path planning form is used; Structural factors: For single-channel multi-layer thin-walled structures, a reciprocating scanning path planning form is adopted; For multi-channel and multi-layer structures, the path planning form of alternating scanning paths or partitioned scanning is adopted; For large metal components with dimensions up to meters, a symmetrical scanning path is used.
Citation Information
Cited By
Method and system for improving metallurgical bonding strength of multi-material additive manufacturing interface in real time
CN120839084A
